Banking Information System Study Through Enterprise Architecture TOGAF - Fian Bagus Saputra; Elly Rahmania (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The development of information technology has changed different views in Indonesian society today. In the era of the industrial revolution 4.0, all industries including the banking industry have implemented the latest Information Technology in accordance with the needs of the industrial revolution. One of the readiness strategies is to make changes to information technology planning based on Enterprise Archi- tecture. The Enterprise Architecture method of this research uses TOGAF (The Open Group Architec- ture Framework). The goal is to develop business architecture, application architecture, information architecture and technology so that they can adapt to the industrial revolution. The application of En- terprise Architecture needs to perform gap analysis and implementation strategies. Application system development does not need to be done totally, but there are several application systems that need to be changed. The application of Enterprise Architecture can be carried out starting from architectural de- sign, gap analysis to implementation strategies so that they are able to face the industrial revolution 4.0.